Code Mixing in an Indonesia Novel Entitled Teman tapi Menikah - Ifrohatul Fauqoh Nikmah (Journal of English Language Teaching and Cultural Studies, 2019)
The objective of this research was to focus on the use of the English Code Mixing in an Indoensian Novel Entitled Teman Tapi Menikah. The writer used qualitative research for conducting the research. The writer determined the reasons and impact of codemixing in after data has been collected. The  aim of study is to investigate the used of English code mixing in Novel Teman Tapi Menikah writers by Ayudia and Dito. This Novel consist of 206 pages, the writer will collect data by reading the Novel and underline the English Code mixing happen in the Novel. It can be concluded that the data of language variation has been elaborated. the writer found the reason for code switching and code mixing in Pojok Kampong news. They are: Easier to Understand, Maintaining Certain Neutrality when both Codes are used, Asserting Power, Pride, and Status, Eliminating ambiguity, Adopts from other language in Javanese, Declaring Solidarity, Expressing Identity, Express Self Emotion, Conveying the Speaker’s Attitude to the Listener, Being more Informative, Being Incompetent in Finding the Appropriate Word.